The Importance of Value Diversity in Corporate Life - Eastman, Wayne (Business ethics quarterly, 2003)
Donaldson and Dunfee (1999) suggest in a brief discussion that a manager may in some cases rely on his or her own values in making organizational decisions. Our paper examines the role of diversity in values in an organizational context. Our central contention is that value diversity among managers, employees, and other stakeholders on dimensions such as prudence-boldness, clarity-flexibility, and rigor-mercy is highly useful for an organization. We introduce nontechnical models of individual and board decision-making in which value diversity cuts across group interests that would otherwise control the decision. In these models, decision-makers who are influenced by values such as prudence or boldness as well as by their group interests are more likely to avoid suboptimal decisions, because their weaker but not their more intense group interests are likely to be overridden by their cross-cutting value inclinations.